2018
DOI: 10.1088/1361-6560/aacc33
|View full text |Cite
|
Sign up to set email alerts
|

The effects of image homogenisation on simulated transcranial ultrasound propagation

Abstract: Transcranial transmission of ultrasound is increasingly used in a variety of clinical and research applications, including high intensity ablation, opening the blood brain barrier, and neural stimulation. Numerical simulations of ultrasound propagation in the head are used to enable effective transcranial focusing and predict intracranial fields. Such simulations require maps of the acoustic properties of the head, which can be derived from clinical CT images. However, the spatial resolution of these images is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 36 publications
3
12
0
Order By: Relevance
“…This is in agreement with the Robertson et al. study, 67 who showed that the homogenization of acoustic property maps leads to an overestimation in the amplitude of ultrasound and an underestimation of time‐of‐flight. However, smarter homogeneous models can be used to improve computation time without losing too much accuracy.…”
Section: Discussionsupporting
confidence: 92%
“…This is in agreement with the Robertson et al. study, 67 who showed that the homogenization of acoustic property maps leads to an overestimation in the amplitude of ultrasound and an underestimation of time‐of‐flight. However, smarter homogeneous models can be used to improve computation time without losing too much accuracy.…”
Section: Discussionsupporting
confidence: 92%
“…To model acoustic propagation of applied transcranial ultrasound, each participant's coronal MRI slice corresponding to the neuronavigation-captured transducer position was manually segmented into scalp, skull, and brain tissue planes (Hynynen and Sun, 1999;Rosnitskiy et al, 2019) (Appendix 1). The segmented tissue layers were treated as homogenous tissue masks with material properties such as attenuation coefficient, sound velocity, and density derived from the literature (Mueller et al, 2017;Robertson et al, 2018Robertson et al, , 2017. An acoustic simulation toolbox, k-Wave (Treeby and Cox, 2010), was used to generate simulations of the acoustic focus for each participant based on individualized transducer positions acquired via neuronavigation ( Figure 2B-C) and the resulting pressure field was mapped back onto the original MRI images ( Figure 2-Figure supplement 1).…”
Section: Electromagnetic and Acoustic Field Brain Mappingmentioning
confidence: 99%
“…The assumption of bone homogeneity may be insufficient to capture the complexity of ultrasound propagation through vertebral bone, which has been shown to have varying density and complex trabecular structures [44]. Recently, image homogenization has been shown to contribute to the underestimation of transmitted amplitude and time-of-flight in transcranial simulations [45], and is likely to under-predict focal distortions. Additionally, the acoustic properties used in these simulations were based on skull bone, and these may not be transferrable to vertebral bone.…”
Section: Discussionmentioning
confidence: 99%